Dihydroartemisinin Inhibits the Proliferation of Esophageal Squamous Cell Carcinoma Partially by Targeting AKT1 and p70S6K - Lili Zhu; Lili Zhu; Xinhuan Chen; Xinhuan Chen; Yanyan Zhu; Jiace Qin; Jiace Qin; Tingting Niu; Tingting Niu; Yongwei Ding; Yongwei Ding; Yang Xiao; et al. (Frontiers Media S.A., 2020)
Dihydroartemisinin (DHA), a sesquiterpene lactone with endoperoxide bridge, is one of the derivatives of artemisinin. In addition to having good antimalarial properties, DHA exhibits anticancer effects including against malignant solid tumors. However, the mechanism by which DHA inhibits the progression of esophageal cancer, especially esophageal squamous cell carcinoma (ESCC), is unclear. In this study, DHA was found to inhibit the proliferation of ESCC, and the underlying molecular mechanisms were explored. DHA inhibited ESCC cells proliferation and anchorage-independent growth. Flow cytometry analysis revealed that DHA significantly blocked cell cycle in the G1 phase. The results of human phospho-kinase array revealed that DHA downregulated the levels of p70S6KT389 and p70S6KT421/S424. Furthermore, the levels of mTORS2448, p70S6KT389, p70S6KT421/S424 and RPS6S235/S236 were decreased after DHA treatment in KYSE30 and KYSE150 cells. We then explored the proteins targeted by DHA to inhibit the mTOR-p70S6K-RPS6 pathway. Results of the in vitro kinase assay revealed that DHA significantly inhibited phosphorylation of mTORS2448 by binding to AKT1 and p70S6K kinases. In vivo, DHA inhibited the tumor growth of ESCC patient-derived xenografts and weakened p-mTOR, p-p70S6K, and p-RPS6 expression in tumor tissues. Altogether, our results indicate that DHA has antiproliferative effects in ESCC cells and can downregulate mTOR cascade pathway partially by binding to AKT1 and p70S6K. Thus, DHA has considerable potential for the prevention or treatment of ESCC.